Transfer ryzyka życiowego na rynek kapitałowy - Brach, Dominik (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Asset-backed securitization on the financial market started from transactions based on mortgage loans. In course of time new instruments on the financial market appeared based on different kinds of assets and securitization was applied, for example, in car loans, mortgage loans secured by commercial realty and many others. Securitization of insurance market assets was a subsequent stage of the market development. Catastrophe risks were the first ones to undergo the transfer to capital market. At the present moment new solutions emerge - they are based on catastrophe risks and introducing new risks traditionally connected with insurance sector (for example - life risks) to capital market. In the article the idea of life risk transfer to the capital market will be introduced. Previous attempts to gain entities from outside the sector of finacing life risks as well as first successful life risk transaction to the capital market will be discussed. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 64-71